Engaging Institutional Stakeholders to Develop and Implement Guidelines for Recruiting Participants in Research Studies Using Social Media: Mixed Methods, Multi-Phase Process - Elizabeth Flood-Grady; Lauren B Solberg; Claire Baralt; Meghan Meyer; Jeff Stevens; Janice L Krieger (JMIR Publications, 2021)
BackgroundLimited regulatory guidance surrounding the use of social media channels for participant recruitment is an interdisciplinary challenge. Establishing stakeholder-informed procedures is essential for ethical and effective use of social media for participant recruitment. ObjectiveThis study aims to provide replicable procedures for developing and implementing guidelines for using social media to recruit participants in research studies. MethodsSocial media use cases at the university were used to identify institutional stakeholders for the initiative. After establishing workflow procedures, a scoping review of web-based materials about recruitment and research on the internet and social media from 19 peer institutions and 2 federal agencies was conducted to inform the structure of the policies and procedures. End users (investigators and study coordinators; N=14) also provided feedback on the policies and procedures and implementation. ResultsRepresentatives (n=7) from 5 institutional offices and 15 subject-matter experts from 5 areas were identified as stakeholders in the development of policies and procedures. Peers with web-based materials (n=16) identified in the scoping review revealed 4 themes that served as a basis for developing our policies and procedures. End user feedback further informed the policies and procedures and implementation. A centrally managed social media account for communicating with participants and hosting advertising campaigns on social media was also established and, when combined with the policies and procedures, resulted in 39 advertising campaigns, and 2846 participants were enrolled in health and clinical research studies. ConclusionsOur policies and procedures allow research teams to harness the potential of social media to increase study recruitment and participation; the transparent, stakeholder-informed process can be replicated by institutional administrators to establish policies and procedures that meet the interests and needs of their research community.